2020
DOI: 10.1017/s1463423620000043
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation needs in individuals with knee OA in rural Western Cape, South Africa: an exploratory qualitative study

Abstract: Background: Current clinical practice guidelines have suggested that each individual with knee osteoarthritis (OA) should receive three core treatments from their health care provider. These core treatments comprise of exercise, education and weight loss. Identification of the health care and rehabilitation needs of individuals with knee OA in rural areas are imperative for focusing service delivery in a specific context in order to empower the individual. The aim of this study was to explore the rehabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 38 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…In South Africa, access to healthcare is more limited in rural areas where health personnel are often limited to students, new graduates, and medical aides ( 22 ). A qualitative study of people with knee osteoarthritis in rural Western Cape revealed three themes: lack of osteoarthritis education, barriers to osteoarthritis-related healthcare, and physical restrictions, such as reduction in mobility and inability to do household chores, that lowered quality-of-life ( 12 ). Further, South African provinces are governed by different political parties, which impacts the care available in each region, and results in fragmentation of health services ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In South Africa, access to healthcare is more limited in rural areas where health personnel are often limited to students, new graduates, and medical aides ( 22 ). A qualitative study of people with knee osteoarthritis in rural Western Cape revealed three themes: lack of osteoarthritis education, barriers to osteoarthritis-related healthcare, and physical restrictions, such as reduction in mobility and inability to do household chores, that lowered quality-of-life ( 12 ). Further, South African provinces are governed by different political parties, which impacts the care available in each region, and results in fragmentation of health services ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although much of the osteoarthritis care provided in South Africa is in the public primary health clinics, due to poor resourcing there are long waiting times and little support to assist people to self-manage their osteoarthritis ( 12 ). People in Brazil often pay for their own osteoarthritis treatment ( 24 ), as SUS services are limited and the waiting times are also long ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several publications have reported that the primary health care rehabilitation service and workforce are inadequate in South Africa. 12 16 For example, the estimated number of occupational therapists in the country is less than one for every 10 000 people who depend on public health care. 17 Furthermore, therapists are mainly available only in tertiary hospitals and less than a quarter of primary health-care facilities provide rehabilitation on a daily basis.…”
Section: Introductionmentioning
confidence: 99%